2016
DOI: 10.1007/s13149-016-0529-7
|View full text |Cite
|
Sign up to set email alerts
|

Les manifestations cardio-vasculaires au cours du lupus érythémateux systémique à Dakar : étude descriptive à propos de 50 cas

Abstract: Systemic lupus erythematosus is a non-specific inflammatory disorder of an organ of unknown cause and autoimmune origin. Visceral injuries, including those cardiovascular, determine the prognosis of this disease primarily affecting women. The objectives of this study were to determine the frequency and describe the cardiovascular manifestations in systemic lupus erythematosus in a lupus population of the Dakar region. This is a multicenter prospective study descriptive and analytical conducted in the region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
4
3
3
Order By: Relevance
“…The reason for admission was dominated by prolonged fever (34.8%). Our results were not similar to the work of Ngaïdé et al [3] in Senegal who found that the symptomatology was dominated by dyspnea stages II and IV according to NYHA, at 26%. Our results could be explained by the fact that systemic inflammatory diseases are known to be etiologies of prolonged fever and especially in a tropical context.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The reason for admission was dominated by prolonged fever (34.8%). Our results were not similar to the work of Ngaïdé et al [3] in Senegal who found that the symptomatology was dominated by dyspnea stages II and IV according to NYHA, at 26%. Our results could be explained by the fact that systemic inflammatory diseases are known to be etiologies of prolonged fever and especially in a tropical context.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study population was predominantly female with a male to female sex ratio of 0.1. This female predominance was similar to that of several others such as Ngaïdé et al in Senegal [3] and Tazi-Mezalek et al in Morocco [4]. Estrogens are thought to increase the secretion of prolactin and growth hormones, which in turn may play a role in the proliferation of T and B lymphocytes [5], androgen deficiency may be associated with the development of immune-related events [6].…”
Section: Discussionsupporting
confidence: 84%
“…A clear female predominance with a male to female sex ratio of 0.09 was found. This female predominance was also found by several other authors [5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 88%
“…Pericarditis represents the most common cardiac involvement in rheumatoid arthritis. This result is superior to that of Kapkovi et al [11] in Togo who had noted it in 1.1% of patients and is inferior to that of Ngaïdé et al [8] in Senegal who had found 38% of pericarditis during lupus pathology. This could be explained by the fact that the majority of patients were already under specific treatment, which would have already improved the pericardial effusion.…”
Section: Discussioncontrasting
confidence: 84%
“…Few published reports on cardiovascular complications of SLE in African populations exist [21–23], although a recent study described high severity of lupus myocarditis in adult SLE patients in Cape Town [24]. A similar study of 50 adult patients in Senegal reported 3 cases of cardiomyopathy and 19 cases of pericarditis, 2 with tamponade physiology [25].…”
Section: Introductionmentioning
confidence: 99%